Overview of the Quality of Life of Fishing Communities - Zahra, Siti; Fitri, Siti Yuyun Rahayu; Fitri, Siti Ulfa Rifa’atul (GLOBAL HEALTH SCIENCE GROUP, 2024)
Fishing communities face hazardous working environments, health problems due to high workloads and consumption of addictive substances, long working periods, low levels of education, and uncertain incomes that lead to disruptions in their quality of life. Objective: This study aims to determine the description of the quality of life of fishermen in Bojong Salawe Village based on 4 aspects of the dimensions of physical health, psychological health, social relationships, and the environment. Method: This research design is quantitative with descriptive method. The study used simple random sampling method with a sample size of 68 fishermen at Bojongsalawe Beach. Instrumen penelitian ini menggunakan World Health Organization Quality of Life - Abbreviated Form (WHOQoL-BREF). The WHOQoL-BREF measuring instrument has a Tucker-Lewis index (TLI) value = 0.86 and Cronbach's Alpha value of the WHOQOL-BREF questionnaire is 0.89. The analytical tool used is univariate to analyze one variable Results: The results of this study showed that more than most respondents (52.9%) had a low level of quality of life category. The physical health (58.8%), psychological well-being (60.3%) social (37.7%) and environmental (42.6%) dimensions of well-being were analyzed. Conclusions : Optimization of central government policies related to health aspects, provision of fisheries business facilities and infrastructure, training and access to equitable and sustainable sanitation for both fishermen and fishermen's families at Bojongsalawe Beach and occupational health services for fishermen.